2016
DOI: 10.1016/j.pmn.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Pain, Disability, and Sex in African Americans

Abstract: Older African Americans consistently report diminished capacities to perform activities of daily living (ADL) compared to other race groups. It remains unclear the extent to which bodily pain is related to declining abilities to perform ADL/ADL disability in African Americans and if this relationship exists in both African American men and women to the same degree. In order for nurses to provide optimal care for older African Americans, a better understanding of the relationship between bodily pain and ADL dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Similarly, gender differences in pain and disability have been described in prior research and thus our rationale for controlling for this variable during analysis. (Walker et al, 2016) Thus, the current study supports that gender may be a valuable modifying variable to consider for both clinical researchers and clinical practitioners in attempts to improve disability in pain populations.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, gender differences in pain and disability have been described in prior research and thus our rationale for controlling for this variable during analysis. (Walker et al, 2016) Thus, the current study supports that gender may be a valuable modifying variable to consider for both clinical researchers and clinical practitioners in attempts to improve disability in pain populations.…”
Section: Discussionsupporting
confidence: 71%
“…Older and middle-aged African American women are at a particularly high risk of experiencing pain and subsequent pain-related disability because of the intersection of their sex, age, race, and high rates of chronic conditions such as osteoarthritis (OA) (Baker & Green, 2005; Baker, Buchanan, & Corson, 2008; Baker, Buchanan, Small, Hines, & Whitfield, 2011; Walker et al, 2016b). Furthermore, pain is common among adults with OA (Arthritis Foundation, 2015), and women experience higher rates of OA after the age of 50 than men (Buckwalter, Saltzman, & Brown, 2004).…”
mentioning
confidence: 99%
“…Furthermore, pain is common among adults with OA (Arthritis Foundation, 2015), and women experience higher rates of OA after the age of 50 than men (Buckwalter, Saltzman, & Brown, 2004). This places African American women with OA at high risk of experiencing pain caused by OA and possibly other chronic conditions (Baker et al, 2011; Walker et al, 2016b). Among African American women, pain is related to poor physical function and more disability (Allen et al, 2012; Baker & Whitfield, 2015; Bolen et al, 2010; Jordan et al, 2007; Keefe et al, 2000; Parmelee et al 2012).…”
mentioning
confidence: 99%
“…In addition to having their pain underaccessed, they are less likely to receive opioid and nonopioid-based medications [10][11][12]. A study analyzing data from a dataset within the Baltimore Study of Black Aging series, assessed activities of daily living (ADL) and pain in older African American adults [13]. Results showed that bodily pain and two or more comorbidities were significantly associated with ADL disability.…”
Section: Pain Mismanagementmentioning
confidence: 99%